FORMATION OF CULTURE OF PROFESSIONAL COMMUNICATION AS A COMPONENT OF THE PROFESSIONAL CULTURE OF THE FUTURE AGRICULTURAL SPECIALISTS (Pedagogy of Higher and Secondary Education, 2008)
The article is dedicated to the question of “professional culture ” and to analyses of ways of professional culture formation of agrarian students by means of foreign languages.